2023
DOI: 10.1038/s41443-023-00687-4
|View full text |Cite
|
Sign up to set email alerts
|

Prior COVID-19 infection associated with increased risk of newly diagnosed erectile dysfunction

Abstract: We sought to assess if COVID-19 infection recovery is associated with increased rates of newly diagnosed erectile dysfunction. Using IBM MarketScan, a commercial claims database, men with prior COVID-19 infection were identified using ICD-10 diagnosis codes. Using this cohort along with an age-matched cohort of men without prior COVID-19 infection, we assessed the incidence of newly diagnosed erectile dysfunction. Covariates were assessed using a multivariable model to determine association of prior COVID-19 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This technical and clinical progress might, in turn, lead to an increased public exploration of the subject matter [17]. Additionally, lifestyle changes and external factors such as libido, psychological stress, and the questionable relationship between COVID-19 and ED during and/or after the pandemic likely contributes to the intensified search interest [19,20]. The compounded of COVID-19 and psychogenic disorders stemming from isolation, grief, and anxiety could contribute to the increased prevalence of ED, which may be further exacerbated by the emergence of preexisting sleep disorders or those induced by the pandemic [20].…”
Section: Discussionmentioning
confidence: 99%
“…This technical and clinical progress might, in turn, lead to an increased public exploration of the subject matter [17]. Additionally, lifestyle changes and external factors such as libido, psychological stress, and the questionable relationship between COVID-19 and ED during and/or after the pandemic likely contributes to the intensified search interest [19,20]. The compounded of COVID-19 and psychogenic disorders stemming from isolation, grief, and anxiety could contribute to the increased prevalence of ED, which may be further exacerbated by the emergence of preexisting sleep disorders or those induced by the pandemic [20].…”
Section: Discussionmentioning
confidence: 99%
“…Compared men with prior COVID-19 infection to men without documented COVID-19 infection. They all reported that newly diagnosed erectile dysfunction is higher in men with prior COVID-19 compared to age-matched control ( 47 49 ).…”
Section: Effect Of Sars-cov-2 On Reproductive Tissuesmentioning
confidence: 99%
“…Over the past few decades, a good amount of evidence supports erectile function as an excellent indicator of systemic health in general and vascular health in particular ( 46 ), effects of COVID-19 on the cardiovascular system (i.e., acute cardiac injury, myocarditis) as well growing evidence in the role of endothelial cell dysfunction during COVID-19 infection most importantly, the endothelium expresses the ACE2 led many have hypothesized there may be an increased risk of Erectile dysfunction (ED) following COVID-19 ( 47 ).…”
Section: Effect Of Sars-cov-2 On Reproductive Tissuesmentioning
confidence: 99%
“…Due to local immune system activity, which may result in deleterious effects in this immuneprivileged organ (37), leukocyte infiltration combined with inflammatory cytokines can have detrimental effects on the function of Leydig cells, which are outside the BTB, leading to impaired testosterone production as well as damage to the BTB (38,39). Infection with SARS-CoV-2 can be associated with a decrease in testosterone levels, testicular pain, erectile dysfunction, and histopathological lesions in severe cases (23,30,(38)(39)(40).…”
Section: Testicular Infection By Sars-cov-2mentioning
confidence: 99%
“…Pre-existing diseases such as diabetes, obesity, hypertension, and cardiovascular disease can increase SARS-CoV-2 infection, leading to a higher risk of severe illness and histopathological damage ( 7 , 28 , 29 ). Among men who had confirmed COVID-19 infection, a higher proportion of individuals had pre-existing conditions such as diabetes mellitus, hyperlipidemia, hypertension, and hypogonadism ( 30 ). Additionally, diabetes and obesity are associated with lowered testosterone levels, testicular dysfunction, and inflammation, which can compromise the MRT ( 31 ).…”
Section: Introductionmentioning
confidence: 99%